The effectiveness of using reciprocal teaching to memorize the multiplication tables among third-grade students in Al-Kharj - Aldosari, Sarah Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to identify the effectiveness of the use of reciprocal teaching in memorizing the multiplication table among third-grade students. The study used the quasi-experimental approach, and the tool was represented in a teacher’s guide that was designed in two units of multiplication, the fourth and fifth, according to the procedures of reciprocal teaching. The pre and posttest was applied to a sample of (38) female students. It was divided into two groups, a control group, which numbered (19) students, and an experimental group, which numbered (19) students. The results of the study showed that there were statistically significant differences between the average results of the two experimental groups; And I got an overall average (24.61 out of 30), in return for the control group obtaining an overall average of (14.39 out of 30),Where the value of the Mann Whitney test (U) Mann-Whitney (83.500), which is a value and the differences are statistically significant at the level of significance (0.05 ≥α) and in favor of the experimental, because the value of the significance level associated with it reached (0.004) which is less than the required significance level (0.05), which indicates the effectiveness of using reciprocal teaching to memorize the multiplication tables for the third grade students in Al-Kharj Governorate. Based on the results, the researcher recommended the mathematics teachers’ research to prepare a teacher’s guide in one of the study units according to the reciprocal teaching procedures, and to apply the use of the effectiveness of reciprocal teaching in improving the mathematical skills of students with learning difficulties., and urged teachers and supervisors to participate in the production of units of study in mathematics based on the use of reciprocal teaching.